Pengaruh Penggunaan Tepung Limbah Roti dan Tepung Keong Mas (Pomacea canaliculata Lamarck) dalam Ransum Burung Puyuh terhadap Konsumsi Protein, Produksi Telur dan Bobot Telur - Alfian Asri; Harissatria; Dara Surtina (Program Studi Peternakan, 2021)
This study aimed to determine the effect of using bread waste flour (BWF) and golden snail flour (GSF) in the ration of quail on protein consumption, egg production and egg weight. The design used was a completely randomized design (CRD) with treatment levels of the use of BWF and GSF in the ration, namely P0 (using yellow corn and fish meal without BWF and GSF), P1 (10% BWF and 5,35% GSF), P2 (20% BWF and 10,65% GSF), P3 (30% BWF and 16% GSF). Each treatment consisted of 5 cage units as replicates. Each cage unit is filled with 4 quails. The results showed that using BWF and GSF with levels of 30% and 16% (P3) resulted in no significant difference in protein consumption, egg production and quail egg weight. It can be concluded that using 30% bread waste flour (BWF) and 16% golden snail flour (GSF) in quail rations during the egg-laying period did not make any difference to all the variables measured.